2016
DOI: 10.1002/mame.201600292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Octyltetramethyldisiloxane‐Containing Ethylene Copolymers as Composite Lubricant for High‐Density Polyethylene

Abstract: A series of octyltetramethyldisiloxane‐containing ethylene copolymers, poly(ethylene‐co‐OO7) (abbreviated as E‐co‐OO7), are prepared from vanadium catalyzed copolymerization of ethylene with 1‐oct(7‐en)yl‐3‐octyl‐1,1,3,3‐tetramethyldisiloxane (or OO7) macromonomer. The copolymers containing different silicone contents are employed as composite lubricants for high‐density polyethylene (HDPE). The influences of the silicone content in the copolymer and that of the added copolymer amount in the blend on the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Beyond the application of PP ‐g‐ PDMS as a compatilizer for PP/PDMS blend, it may also function as a processing aid for high‐viscosity PP that make an injected or molded product both possible and profitable . Jin et al illustrated that siloxane‐containing ethylene copolymer can serve as an effective multifunctional/composite lubricant for high‐density polyethylene and exhibits overall superior performance in comparison with conventional internal (PE wax) or external (silicone masterbatch) lubricants, since it strikes a good balance between soluble flow‐enhancing lubrication and insoluble surface‐modifying lubrication. PP ‐g‐ PDMS, a novel silicone‐containing PP‐based copolymer and moderately soluble in PP matrix, is likely to reduce the friction between PP macromolecular chains when they sliding against each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the application of PP ‐g‐ PDMS as a compatilizer for PP/PDMS blend, it may also function as a processing aid for high‐viscosity PP that make an injected or molded product both possible and profitable . Jin et al illustrated that siloxane‐containing ethylene copolymer can serve as an effective multifunctional/composite lubricant for high‐density polyethylene and exhibits overall superior performance in comparison with conventional internal (PE wax) or external (silicone masterbatch) lubricants, since it strikes a good balance between soluble flow‐enhancing lubrication and insoluble surface‐modifying lubrication. PP ‐g‐ PDMS, a novel silicone‐containing PP‐based copolymer and moderately soluble in PP matrix, is likely to reduce the friction between PP macromolecular chains when they sliding against each other.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the application of PP-g-PDMS as a compatilizer for PP/PDMS blend, it may also function as a processing aid for highviscosity PP that make an injected or molded product both possible and profitable. 14,17 Jin et al 18 The complex viscosity curves of pure PP and its blend with PP-g-PDMS were shown in Figure 11. The results show that dynamic complex viscosity of PP/PP-g-PDMS blend decreased dramatically compared with pure PP in whole frequency range (0.1-100 rad/s).…”
Section: Potential Applications Of Pp-g-pdmsmentioning
confidence: 99%
“…The supported phosphinephenolate Ni catalyst 10a-Na-MgO was used for the synthesis of ethylene and n-butyl Vinyltrimethoxysilane (VTMOS) is easier to copolymerize with ethylene than other fundamental polar monomers because it has lower toxicity for the catalyst. The functional polyethylenes containing silicon-oxygen bonds can serve as versatile processing additives [89,90]. Homogeneous imine-bridged bisphosphine-monoxide Ni catalysts 6b and 6d, as well as the heterogeneous phosphine-phenolate Ni catalyst 10a-Na-MgO, have been reported for synthesizing ethylene and VTMOS copolymers at 80 °C (Table 3, Entries 1-3) [62,70].…”
Section: Polar Monomersmentioning
confidence: 99%
“…Recently, nanosized and high crystalline cellulose with high rigidity, tensile stiffness, and shear force has attracted much attention due to its intrinsic properties (Habibi 2014;Wang et al 2018). Thus, cellulose nanocrystals (CNCs) can be used as a reinforcing material to improve surface and antifouling properties of polymers (Jin et al 2016;Rodrigues et al 2017;Bai et al 2019). In addition, CNCs possess hydroxyl groups and can be modified by oxidation, esterification, etherification, and grafting copolymerization (Liu et al 2017a).…”
Section: Introductionmentioning
confidence: 99%